On the carcino-group bycatch in the industrial fishery for southern brown shrimp on the Amazon continental shelf (Research, Society and Development, 2020)
This work was carried out with the objective of quantifying the carcino-group present in the bycatch of the southern brown shrimp industrial fishery on the Amazon Continental Shelf by season, period of the day and depth range. The study was carried out from 152 records of fishing operations or bottom trawls, 72 in the rainy season (December to May) and 80 in the dry season (June to November), with an average duration of 3.5 ± 1.5 hours, totaling 532 hours of trawling, in the months of July and September 2010 and March and April 2011, between the states of Pará and Amapá. Initially, the bycatch was classified into five groups: fish, southern brown shrimp, crustaceans, mollusks and others. After that, the crustaceans were screened: crabs, portunids, shrimps, lobsters and stomatopods, where each group was quantified in weight and number of specimens. From the samples collected during the study period, we observed a southern brown shrimp /bycatch ratio of 1:3 in the rainy season, and of 1:30 in the dry season. Carcino-group differed significantly between the seasons and the depth range, but not along the day. The ratio between the amount (kg) of captured southern brown shrimp and carcino-group bycatch oscillated greatly, with the average value of 1:1. In industrial fisheries for southern brown shrimp on the northern coast of Brazil, the southern brown shrimp/carcino-group bycatch ratio is influenced by the season and depth range, and is less harmful to the biodiversity in the first semester of each year.